The influence of the emission of sound energy from communication routes and other places of energy consumption on human health - Kaźmierczak, Urszula; Kulczycki, Andrzej (Studia Ecologiae et Bioethicae, 2012)
This article aims to draw attention to the hitherto unexplored and scarcely noticed the problem of the effects of the consumption of increasing amounts of energy to human health and ecosystems exposed to emissions processed in the phase of energy consumption. Ever-increasing amounts of energy are consumed in relatively small areas of highways. Reference is made to the results of pioneering research on the impact of emitted sound energy by transport routes and by industrial noise on human health (Borzyszkowski 2010). This was clearly found to increase in people exposed to prolonged acoustic wave energy. The results of the effect of noise on human health clearly indicate the need for further research in this field. It should be emphasized that although the research and evaluation conducted by the Institute for Environmental Protection and Proeko CDM Ltd., which have been presented in this article, are pioneering and include an analysis of the cause-and-effect phenomenon, they do not, however, indicate the mechanism of the effect of noise on human health. The category rating of disease symptoms caused by the noise indicates that the key to clarifying the influence of the energy supplied to the organisms of people on the way of acoustic waves on their health may be forced supplied energy changes of biochemical reactions occurring in humans.